Stand by me 2.0. Visits by family members at Covid-19 time - Carlucci, Matilde; Carpagnano, Lucia Federica; Dalfino, Lidia; Grasso, Salvatore; Migliore, Giovanni (Acta Biomedica Atenei Parmensis, 2020)
Background: In the complex health emergency situation of our country, the application of Information Technology tools has a decisive role in supporting health insurance, creating a highly performing and technologically advanced system that reduce distances, suffering of disease and the weight of necessary isolation. The theme of the humanization of care, understood as attention to the person as a whole, is a highly topical issue today. The humanization in the healthcare is intended as the ability to make the places of care and the same medical care practices more open, safer and painless, reconciling hospitality, information and comfort with care paths as much as possible in sharing with the patient and his family. Materials and Methods: Pursuing the purposes inherent in the concept of humanization of care and assistance, with the aim of offering Apulian citizens a complementary, but also fundamental, service in clinical-therapeutic assistance to the patient affected by COVID-19, in the hope of improving the quality of care, also in relation to the perception of the user, the Strategic Management of the AOU Policlinico of Bari has launched an experimental project that fits into the context of care quality, a crucial and not negligible issue, despite the extreme difficulties dictated by the ongoing medical emergency. Results: The experimental project proposes an innovative clinical-organizational model which, through Information and Communications Technology (ICT), intends to make the management of COVID-19 patients optimal, safe and better, in all the spheres that jointly define the concept of Health.